2002
DOI: 10.1128/aem.68.5.2209-2213.2002
|View full text |Cite
|
Sign up to set email alerts
|

Rapid PCR-Based Method Which Can Determine Both Phenotype and Genotype of Lactococcus lactis Subspecies

Abstract: A highly efficient, rapid, and reliable PCR-based method for distinguishing Lactococcus lactis subspecies (L. lactis subsp. lactis and L. lactis subsp. cremoris) is described. Primers complementary to positions in the glutamate decarboxylase gene have been constructed. PCR analysis with extracted DNA or with cells of different L. lactis strains resulted in specific fragments. The length polymorphism of the PCR fragments allowed a clear distinction of the L. lactis subspecies. The amplified fragment length poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 15 publications
1
49
0
Order By: Relevance
“…lactis strains are GAD ϩ , L. lactis subsp. cremoris strains, as a consequence of inactivation of their gadB gene by a frameshift mutation, do not possess GAD activity (20). Thus, to further investigate the link between the mutation, natural or otherwise, of GAD and nisin sensitivity, a selection of L. lactis subsp.…”
Section: Resultsmentioning
confidence: 99%
“…lactis strains are GAD ϩ , L. lactis subsp. cremoris strains, as a consequence of inactivation of their gadB gene by a frameshift mutation, do not possess GAD activity (20). Thus, to further investigate the link between the mutation, natural or otherwise, of GAD and nisin sensitivity, a selection of L. lactis subsp.…”
Section: Resultsmentioning
confidence: 99%
“…A 600 bp PCR fragment derived from the gadB gene should be obtained from the chromosomal DNA of the strains tested if the strain belongs to L. lactis subsp. lactis 20 . Fig.1 showed that DNA from the tested strains generated fragments corresponding to the 600 bp fragment of L. lactis subsp.…”
Section: Resultsmentioning
confidence: 99%
“…A 600 bp PCR fragment should be obtained from the chromosomal DNA of the strains tested if the strain belongs to L. lactis subsp. lactis 20 .…”
Section: Identification Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(13,14). Reliable PCR methods for confirmation of the species L. lactis and its two subspecies lactis and cremoris as well as for detection of DNA sequences related to the presence of each of the above genes have been developed (10,12,13).…”
Section: Introductionmentioning
confidence: 99%